Learning Style: Visual, Auditory and Kinesthetic - Mahadi, Faridah; Husin, Mohd Razimi; Md Hassan, Nurulhuda (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Gaya pembelajaran adalah cara bagaimana pelajar menyerap dan menyusun maklumat yang diterima. Pendekatan gaya pembelajaran secara umum terbahagi kepada tiga aspek; visual, auditori dan kinestetik. Pertama, gaya visual, yang belajar paling berkesan ketika melihat pembelajaran dengan media gambar. Kedua gaya auditorial, yang berkesan belajar melalui suara yang didengar. Maka gaya pembelajaran pendengaran adalah gaya pembelajaran dengan mendengar. Pelajar dengan gaya pembelajaran ini lebih dominan menggunakan deria pendengaran ketika menjalankan proses pembelajaran dan pengajaran. Gaya pembelajaran visual suka kemahiran dan kemas, ingin bercakap pantas, suka membuat perancangan yang teliti untuk jangka masa depan, sangat terperinci dengan terperinci. Ketiga, gaya aktif, atau apa yang disebut pelajar kinestetik. Sementara itu, gaya pembelajaran kinestetik adalah dengan bergerak, menyentuh, dan bekerja. Mereka belajar dengan mengutamakan perasaan dan pergerakan fizikal mereka. Penerapan gaya pembelajaran ini dalam aktiviti pembelajaran telah menghasilkan pelbagai kesan positif dalam arena pendidikan. Learning Style: Visual, Auditory and Kinesthetic Abstract: Learning style is the way how students absorb and compose the information received. The learning style approach is generally divided into three aspects; visual, auditory and kinesthetic. First, the visual style, which makes learning the most memorable when looking at learning with image media. Both styles are auditory, which impresses learning through the sound that is heard. Then the hearing learning style is a listening learning style. Students with this learning style are more dominant in using the sense of hearing when carrying out the learning and teaching process. Visual learning style likes skill and order, wants to speak quickly, likes to make careful plans for the future, and is very detailed in detail. Third, active style, or what is called a kinesthetic learner. Meanwhile, the kinesthetic learning style is by moving, touching, and working. They learn by prioritizing their feelings and physical movements. The application of this learning style in learning activities has produced various positive impressions in the educational arena. Keywords: Auditory, Kinesthetic, Learning Style, VAK, Visual.